Existem novos determinantes, além dos clássicos, que podem ajudar a explicar a estrutura de capitais das empresas? - Mamede, Samuel de Paiva Naves (2019)
It is essential to have a knowledge about the theories of Trade Off, Pecking Order and Agency, to understand that there is still a puzzle to be solved: they are not able to explain which are the determinants that companies should choose in the analysis of the capital structure. The main objective of this research is to analyze the impacts of the choice of new factors and/or determinants of the capital structure of companies. The logical intuition is based on the relationship and interaction of classic variables, widely used in the financial and accounting area, counting on the CEO skills, as well as on the use of restricted factors such as corruption, immigration and refugees. Through econometric procedures, such as cross-sectional analysis, panel data and moderation of instrumental variables, this research was composed of 1.675 American companies, extracted directly from the Wharton Research Data Service database, for a period from 2010 to 2017. This research offers a novelty with respect to the identification, interaction and discussion of new factors in the choice of the determinants of the capital structure, since these elements can add value to the companies’ indebtedness policy, although they have never been fully used. Overall, the results of this study provide empirical evidence that the level of corruption in an economy has a direct and positive effect, assuming the following findings: (i) corruption is significant in environments with a higher concentration of refugees, which brings a direct and positive relationship with the level of indebtedness of organizations located in the states that absorb this workforce; (ii) with respect to refugee groups, the companies that adhere to the program for receiving refugees in the states, through the state government, have the following characteristics: ability to obtain easier credit from financial institutions, through the reduction of interest rates, generating the direct impact on their capital structure and, naturally, becoming more competitive with respect to their competitors. Some sectors, such as energy, telecommunications and retail, are finding ways to integrate refugees into their workforces, or to directly support refugee-owned businesses, so that they can participate in easier credit opportunities also create new businesses with the public body. Consequently, the creation of new businesses with the public body over the years, influence the sharing of corrupt acts or illegal benefit between both parties.